Design of a piston-cylinder mechanism for vortex ring formation - Ng, Wei Kiat (2016)
This report gives detail of the design improvement done on the piston- cylinder mechanism used for generating vortex ring and observation done from the set-up to for impingement of vortex ring onto a concave surface. Based on the design review the existing design of the piston and cylinder mechanism use by Kuan, (2013) [1], there is a need to improve the design. With the re-designed of the vortex ring piston ring cylinder which consist of using a close coupled design and proper design of O-ring usage, it was able to produce consistent result without any leakages during operation. The observation was used to compare mainly with 2 journals done by Couch & Krueger (2011) [2] and New et al. (2016) [3] with a comparison flat surface. In the experiment, the dynamics of the circular vortex ring with Reynolds number Re=2000 and Re=4000 was observed 2 dimensionally using laser induce fluorescence visualization. From the result, it is very similar as described and for concave surface, a vortex dipole and small vortex ring-like structure are produced when the vortex ring impinged on to the concave surface with a diameter of 120mm.